Bilateral Lumbar Hernias Following Spine Surgery: A Case Report and Laparoscopic Transabdominal Repair - Marc Rafols; Daniel Bergholz; Anthony Andreoni; Chase Knickerbocker; Jennifer Davies; Robert A. Grossman (Case Reports in Surgery)
Lumbar hernias are rare abdominal wall defects. Fewer than 400 cases have been reported in the literature and account for 2% of all abdominal wall hernias. Lumbar hernias are divided into Grynfelt-Lesshaft or Petit hernias. The former are hernia defects through the superior lumbar triangle, while the latter are defects of the inferior lumbar triangle. Primary lumbar hernias are further subdivided into congenital or acquired hernias and can further be classified as either primary or secondary. Secondary hernias occur after previous flank surgeries, iatrogenic muscular disruption, infection, or trauma. We review a rare presentation of metachronous symptomatic bilateral secondary acquired lumbar hernia following spine surgery. A successful laparoscopic transabdominal lumbar hernia repair with extraperitoneal mesh placement was performed, with resolution of the hernia symptoms. An extensive literature review regarding lumbar hernia and different types of repairs was performed.